Effects of Carvedilol on Blood Pressure, Blood Sugar, and Blood Lipids in Elderly Patients with Refractory Hypertension. (27th July 2022) - Zhang, Wen; Deng, Guiming; Hu, Jia; Yan, Ran; Hu, Junliu; Fan, Jianmin
Abstract : Refractory hypertension seriously affects the life safety of patients. To investigate the effect of carvedilol combined with conventional antihypertensive therapy on blood pressure, blood sugar, blood lipids, and cardiovascular and cerebrovascular complications in elderly patients with refractory hypertension, a total of 80 elderly patients with refractory hypertension who were admitted from June 2019 to September 2021 were selected as the retrospective research objects and divided into the observation group and the control group according to the random number table method, 40 cases in each group, and the control group received conventional antihypertensive therapy. On this basis, the observation group was treated with carvedilol, and the effects of blood pressure, blood sugar, blood lipids, and cardiovascular and cerebrovascular complications were analyzed in the two groups. After treatment, the systolic blood pressure, diastolic blood pressure, adrenal medulla (AM), and endothelin (ET) of the observation group were significantly lower than those of the control group, but the heart rate and NO of the observation group were significantly higher than those of the control group. After treatment, the fasting blood glucose, insulin, triacylglycerol (TG), cholesterol (CHO), and low-density lipoprotein (LDL-C) of the observation group were significantly higher than those of the control group, but the ISI and HDL-C of the observation group were significantly lower than those of the control group. After treatment, the levels of IL-1 β, IL-6, TNF- α, UAER, BUN, and SCr in the observation group were significantly lower than those in the control group. The TC of the observation group was lower than that of the control group. Combination therapy has a remarkably stable, sustained, and safe antihypertensive effect on patients with refractory hypertension.